Implementasi PBL Berbasis Lesson Study untuk meningkatkan Keterampilan Argumentasi Mahasiswa: Implementation of Lesson Study Based PBL to improve Students' Argumentation Skills - Khalil, Muhammad; Akbar, Muh. Nur; Ikalor, Allvanialista; Jannah, Raudhatul (Pedagogi Hayati, 2024)
Argumentation skills are important to train in learning, so that students have logical reasoning, a clear and rational view of the things being studied. This research aims to examine the implementation of the lesson study-based problem based learning (PBL) model in improving students' argumentation skills. The method used in this research is classroom action research with a quantitative descriptive approach carried out in two cycles. Data was collected using pretest-posttest instruments, argumentation skills observation sheets (Toulmin's argumentation pattern), and lesson study-based PBL syntax implementation observation sheets. The results showed that there was an increase in the implementation of PBL syntax from cycle I (76.9%) to cycle II (92.3%). Likewise, there was a significant increase in students' argumentation skills in each cycle. In the first cycle, there was an increase in the distribution of posttest scores where the percentage of students began to reach levels 3 and 4, while in the second cycle, there was a further increase where the majority of students managed to reach levels 3 and 4 in argumentation skills. The conclusion of this research is that the implementation of lesson study-based PBL can effectively improve students' argumentation skills. It is recommended that further research conduct an in-depth study of the content in each component of argumentation so that a more holistic understanding of students' argumentation skills is obtained.